Cutaneous disseminated zoonotic sporotrichosis in immunocompetent person - Mohd Taib, Niazlin; Ibrahim, Rosni; Zakariah, Siti Zulaikha; Abdul Aziz, Nurul Izzati; Kamaruzzaman, Nur Hannah (Universiti Putra Malaysia Press, 2024)
A subacute to chronic fungal illness, sporotrichosis is brought on by the dimorphic species Sporothrix. A growing number of cases involve infected wounds exposed to the spore, leading to persistent ulcers that are frequently connected to regional lymphadenopathy. The disseminated form always complicates the infection, but it is rare in immunocompetent persons. Zoonotic transmission of sporotrichosis is on the rise. In this report, we present a case of cutaneous disseminated sporotrichosis in an immunocompetent individual who contracted the infection from an infected cat. The patient exhibited numerous nodules on the hands and lower limbs for four weeks, with an absence of associated symptoms. The diagnosis was confirmed through culture methods and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) systems and treated with 10 days of intravenous amphotericin B and 12 months of oral itraconazole 200 mg BD. We also emphasized the importance of molecular techniques in accurate identification.